Review of Habitus Perspective in Social Cultural Arena on Women's Character in Oka Rusmini's Novel Tempurung - Rd Bily Parancika; Mohammad Aris (Journal Corner of Education, Linguistics, and Literature, 2022)
Social status connects the concept of habitus that occurs from one's life experience which is located in a realm to create relationships between various positions or classes. Thus, the purpose of this research is to produce a new perspective in distinguishing culture and rational thinking in terms of gender and feminism contained in the socio-cultural arena of Balinese women who are still experiencing gender class injustice. This research is a qualitative descriptive study to describe the perspective of habitus and social culture arena in the novel Tempurung by Oka Rusmini. Data obtained through library techniques. The results of this study indicate that there are changes in habitus that take place irrationally, so that it seems to impose and cause acts of violence that cause discrimination from several figures who consciously or not do actions that can marginalize other characters. This research contributes to the science of literary sociology of thought by Pierre Bourdeu and feminist literary criticism.